Comparison of a Circular Patch Unit Cell Performance for Reflector Applications between Using FR4 and F4BMX220 Substrates at 3.5 GHz Frequency - Taufiqqurrachman -; Muhammad Kamal Abdul Rahim; Dadin Mahmudin; R. Priyo Hartono Adji; Deni Permana Kurniadi; Winy Desvasari; Sulistyaningsih -; Fajri Darwis; Arief Nur Rahman; Prasetyo Putranto; Arie Setiawan; Aminuddin Rizal (National Research and Innovation Agency, 2023)
This paper presents a performance comparison of the circular patch unit cell as a unit cell for reflector application at 3.5 GHz frequency using a dielectric substrate between FR4 and F4BMX220 substrates. A circular patch is chosen as the unit cell of a reflector because it is commonly used, fabricated, and has a wider bandwidth compared to other structures. A performance comparison of the circular patch on both dielectric substrates is presented in a graph of S-parameters, reflection phase, and operating bandwidth, as well as in the table of dimensions, where the result is performed by simulation using CST software. Based on the simulated results, the F4BMX220 has a better performance compared to the FR4 in terms of the reflection value, operating bandwidth, and dielectric substrate thickness. However, a circular patch diameter when using the F4BMX220 is bigger than when using the FR4 substrate because the FR4 substrate has a higher dielectric constant than the F4BMX220, which is twice the F4BMX220 dielectric constant. Also, the F4BMX220 substrate has a narrower bandwidth compared to the FR4 substrate, which is a difference of around 0.1 GHz. The circular patch when using the F4BMX220 substrate has 0.96 of a reflection value, 0.007 of an absorption value, -6.77° of the reflection phase, and 0.24 GHz of the operating bandwidth at the normal incident wave angle (0°). Also, it can be properly worked if the incident wave angle is moving until 60°. The F4BMX220 substrate has the best performance compared to the FR4 substrate because the reflection value is much better value, even at the incident wave angle of 60°.